2012
DOI: 10.1377/hlthaff.2011.0243
|View full text |Cite|
|
Sign up to set email alerts
|

Durable Medical Equipment And Home Health Among The Largest Contributors To Area Variations In Use Of Medicare Services

Abstract: Most analyses of geographic variation in Medicare spending have focused on total spending. However, focusing on the volume and intensity of specific categories of services delivered to patients could help identify ways to lower costs without having a negative impact on care. We investigated how utilization in thirteen medical service categories in Medicare Parts A and B (for hospital and physician insurance, respectively) varied across sixty communities nationwide. We found considerable geographic variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In contrast to prior studies,[5,17] we analyzed spending variation for hospice services separately from other postacute care services. While postacute facility care, home health, and durable medical equipment were confirmed as drivers of regional spending variation, variation in the use of hospice care demonstrated the opposite association, actually offsetting total spending variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to prior studies,[5,17] we analyzed spending variation for hospice services separately from other postacute care services. While postacute facility care, home health, and durable medical equipment were confirmed as drivers of regional spending variation, variation in the use of hospice care demonstrated the opposite association, actually offsetting total spending variation.…”
Section: Discussionmentioning
confidence: 99%
“…Using health care service categories similar to those in our study, James D. Reschovsky and colleagues found that home health services and durable medical equipment were the leading drivers of regional variation in the general Medicare population. [5] Acute hospital care accounted for 40 percent of total spending but was not found to be a driver of regional variation. The Institute of Medicine (IOM) recently assessed the contribution of seven distinct service categories to regional spending variation among Medicare recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Home health is a major driver of geographical variation in the use of Medicare services. 12 The January 24, 2013, settlement agreement in Jimmo v. Sebelius 13 is likely to expand eligibility for Medicare-paid home health services and may presage further cost increases. 14 Investor ownership of home health agencies has grown rapidly, with for-profits accounting for 62 percent of all agencies in 2010.…”
mentioning
confidence: 99%
“…Geographic variations in health care costs and clinical quality, particularly within the Medicare program, have long been of interest to health care providers, policy makers, and payers, beginning with foundational research by Wennberg and colleagues (Burney, Schieber, Blaxall, & Gabel, 1978;Cromley & Shannon, 1988;Escarce, 1991;Hirth, Tedeschi, & Wheeler 2001;Keating, Landrum, Lamont, Bozeman, & McNeil, 2012;O'Hare, Rodriguez, Hailpern, Larson, & Kurella Tamura, 2010;Reschovsky, Ghosh, Stewart, & Chollet, 2012;Wennberg, 1996;Wennberg & Cooper 1999;Wennberg & Gittelsohn, 1973;Wennberg & Gittelsohn, 1982;Zhang, Baicker, & Newhouse, 2010a, 2010b. The existence of variations in spending across the United States (U.S.) suggests opportunities for gains in efficiency and cost savings.…”
Section: Introductionmentioning
confidence: 99%